Factors influencing serum calcium levels and the incidence of hypocalcemia after parathyroidectomy in primary hyperparathyroidism patients - Mu, Yongliang; Zhao, Yishen; Zhao, Jiannan; Zhao, Qi; Zhang, Yushuai; Li, Yang; Kou, Jiedong; Dionigi, Gianlorenzo; Bian, Xuehai; Sun, Hui (Frontiers in Endocrinology, 2023)
Background: Parathyroidectomy (PTX) is an effective treatment for primary hyperparathyroidism (PHPT) patients. Postoperative hypocalcemia is a common complication after PTX. This study aimed to analyze the factors influencing serum calcium levels and the incidence of hypocalcemia after parathyroidectomy in primary hyperparathyroidism patients.The retrospective study included 270 PHPT patients treated with PTX and collected their demographic and clinical information, as well as their laboratory indices. Factors influencing serum calcium levels and hypocalcemia after PTX in PHPT patients were analyzed using univariate and multifactorial analyses.1. In patients with normal preoperative serum calcium levels(2.20-2.74 mmol/L), the higher the preoperative alkaline phosphatase and serum phosphorus levels, the lower the postoperative serum calcium levels. Furthermore, the higher the preoperative serum calcium levels and the accompanying clinical symptoms, the higher the postoperative serum calcium levels. Low preoperative serum calcium levels were shown to be a risk factor for postoperative hypocalcemia (OR=0.022), and the optimal preoperative serum calcium threshold was 2.625 mmol/L (sensitivity and specificity were 0.587 and 0.712, respectively).2. In the mild preoperative hypercalcemia group(2.75-3.00 mmol/L), the older the patient, the higher the preoperative and postoperative serum calcium levels, the higher the postoperative serum calcium; the lower the alkaline phosphatase and calcitonin levels, the higher the postoperative serum calcium levels. On the other hand, the younger the patient, the more likely hypocalcemia blood was (OR=0.947), with an optimal age threshold of 47.5 years (sensitivity and specificity were 0.543 and 0.754, respectively).3. In the preoperative moderate to severe hypercalcemia group(>3.0mmol/L), patients undergoing a combined contralateral thyroidectomy and a total thyroidectomy had low postoperative serum calcium levels.Patients with different preoperative serum calcium levels had various factors influencing their postoperative serum calcium levels and postoperative hypocalcemia, which facilitated the assessment of their prognosis.